Pronunciation instruction and students’ practice to develop their confidence in efl oral skills (2014)
The aim of this article is to inform on research intended to find out how pronunciation instruction of English as a foreign language was handled in the language classroom with elementary students and also understand if pronunciation instruction had an impact on students’ confidence when using it. In order to do this, a qualitative case study was carried out with learners of elementary English as a foreign language at the Language School of Universidad Veracruzana, Mexico. Class observation, a written text, and semi-structured interviews comprised the data collection instruments. The findings showed that not only teacher pronunciation instruction is necessary when learning English as a foreign language but that a lot of student practice is key to developing and enhancing learners’ pronunciation as well.El objetivo de este artículo es informar acerca de una investigación que pretendió explorar cómo se impartía la enseñanza de la pronunciación a estudiantes de inglés como lengua extranjera de nivel elemental en la Facultad de Idiomas de la Universidad Veracruzana, México. También se buscó entender si la enseñanza de la pronunciación tuvo un impacto en la confianza de los estudiantes al aplicarla. En este estudio de caso de corte cualitativo, las observaciones de clases, un texto escrito y las entrevistas semiestructuradas fueron los instrumentos utilizados para recabar los datos. Los resultados mostraron que no solo se necesita la instrucción del maestro, sino que es necesario que los estudiantes practiquen autónomamente para desarrollar y mejorar la pronunciación de la lengua meta.